2023
DOI: 10.1200/jco.2023.41.16_suppl.8508
|View full text |Cite
|
Sign up to set email alerts
|

Phase II trial of neoadjuvant osimertinib for surgically resectable EGFR-mutated non-small cell lung cancer.

Abstract: 8508 Background: Osimertinib is a third-generation EGFR tyrosine kinase inhibitor (TKI) effective in treating advanced EGFR-mutated non-small cell lung cancer (NSCLC). Adjuvant osimertinib significantly decreases disease recurrence in stage IB-IIIA EGFR-mutated NSCLC. However, the benefit of neoadjuvant osimertinib prior to surgical resection remains unknown. Methods: This was a multi-institutional phase II trial of neoadjuvant osimertinib for patients with surgically resectable stage I-IIIA (AJCC V7) EGFR-mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Median DFS was 32 months with immature OS data. There were two grade 3 AEs (pulmonary embolism and atrial fibrillation) ( 49 ). The study also noted that in 4 of 6 patients who did not achieve a pathologic response, there was a loss of function mutation in RBM10 ( 50 ).…”
Section: Neoadjuvant Strategiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Median DFS was 32 months with immature OS data. There were two grade 3 AEs (pulmonary embolism and atrial fibrillation) ( 49 ). The study also noted that in 4 of 6 patients who did not achieve a pathologic response, there was a loss of function mutation in RBM10 ( 50 ).…”
Section: Neoadjuvant Strategiesmentioning
confidence: 99%
“…The NADIM II trial (2023) was a randomized phase II trial that showed that patients with resectable stage IIIA or IIIB NSCLC who received neoadjuvant nivolumab and platinum-based chemotherapy compared to neoadjuvant chemotherapy alone had a greater PCR (37% vs. 7%), greater MPR (53% vs. 14%), overall response (75% vs. 48%), improved 2-year PFS (67.2% vs. 40.9%), and greater 2-year OS (85% vs. 63.6%) (32). Patients who were treated with the combination neoadjuvant nivolumab and chemotherapy and who had PD-L1 expression of ≥ 1% had the greatest improvement in PCR rates.…”
Section: Neoadjuvant Immunotherapy and Chemotherapymentioning
confidence: 99%
See 2 more Smart Citations
“…The downstaging rate was 53.3% when osimertinib was used as a neoadjuvant treatment strategy in patients with EGFR-mutated stage II-IIIB NSCLC [135,136]. Recently, another phase II singlearm trial testing the efficacy of neoadjuvant osimertinib in EGFR-mutated NSCLC also showed negative results: 15% MPR, 0% pCR, and 44% lymph node downstaging rate [137]. Considering these findings, the efficacy of neoadjuvant TKI therapy is unsatisfactory, despite the use of third-generation EGFR-TKIs (Table 8).…”
Section: Neoadjuvant Targeted Therapy In Resectable Egfr-mutated La-n...mentioning
confidence: 99%